DETERMINANTS OF TERROR ACTS ACCOMPLISHES-SUICIDE BOMBERS BEHAVIOR - Buciunas, Gediminas (Administrative and Criminal Justice, 2018)
The aim of this paper is to analyze determinants which impact on behaviour of terror acts accomplishes-suicide bombers from psychological point of view, for example, whether there is a direct connection between Moon phases and suicide terrorists who conducted terror acts from 2015 to 2016 in the different parts of the world. The author also analyzes randomly selected terror acts carried out between 2016 and 2017 in the continent of Europe. Several factors have been taken into account, such as: terror acts location, suicide terrorist’s citizenship, country of origin, age, education, criminal background, country’s unemployment rate.The novelty of this paper is the fact that this type of research was not been carried out yet. This will allow us to see a more precise direction which should be taken in order to effectively prevent terror acts and what kind of changes can be carried out in certain programs for identification of individuals who may be posed real threat to country’s national security, can be easier involved into terror organizations activities than others.